Trinidad and Tobago : 2003 Article IV Consultation-Staff Report; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for Trinidad and Tobago. (IMF Staff Country Reports; Country Report ;, 2003)
Trinidad and Tobago has enjoyed positive growth, low inflation, and a steady decline in unemployment, but challenges remain. Executive Directors commended the prudent management, and stressed the need for a macroeconomic framework underpinned by a three-year rolling budget and pension reform. They welcomed Trinidad and Tobago's role as a regional financial center, the soundness of the banking system, and structural reforms. They emphasized the need to tighten fiscal and monetary policies, and encouraged Trinidad and Tobago to participate in the general data dissemination system.